Effects of Interactive Feedback and Learning Proficiency on Chinese EFL Learners’ Affective Engagement - Chen Zhao (Journal of Linguistics and Communication Studies, 2025)
Using Python semantic orientation analysis and SPSS 26.0 to analyze group discussion text of 72 non-English major graduate students, this study investigates the effects of interactive feedback and English learning proficiency on EFL learners’ affective engagement in English collaborative learning. The study found that: (1) Interactive feedback positively influenced affective engagement, while the experimental group elicited significantly higher affective engagement than the control group, with richer emotional experiences and enhanced interactivity. (2) Significant differences existed in the effects of English learning proficiency on learners’ affective engagement, with high-proficiency learners exhibiting greater engagement than low-proficiency peers. (3) Interactive feedback and English learning proficiency levels had a significant interaction effect on learners’ affective engagement. High-proficiency learners in AWE-teacher-peer feedback demonstrated the highest engagement, followed by high-proficiency learners in teacher-peer feedback, low-proficiency learners in AWE-teacher-peer feedback and low-proficiency learners in teacher-peer feedback. These findings offer valuable insights that can guide educators in providing appropriate affordance and emotional support to effectively stimulate learners’ affective engagement in English learning.